Effects of Three Exercise Interventions on Pregnancy and Neonatal Outcomes in Chinese Women with Gestational Diabetes Mellitus: A Prospective Cohort Study - Yingchun Zeng; Xiaohui Meng; Meiling Wen; Yin Qin; Xiaorong Wang; Xia Dai; Qiuhong Huang (IMR Press, 2024)
Background: Gestational diabetes mellitus (GDM) is the most common metabolic disorder occurring during pregnancy. It affects 14.8% of pregnancies among Chinese women. Exercise can reduce insulin resistance and thus decrease the occurrence of adverse outcomes for women with GDM. This study aimed to examine the effects of three modes of exercise intervention on glycemic control, various pregnancy outcomes (including reduced incidence of preterm birth, gestational hypertension, and postpartum hemorrhage), and neonatal outcomes (such as lower birth weight and reduced incidence of neonatal complications like macrosomia and respiratory distress syndrome). Additionally, the study aim to identity the most effective exercise patterns for women with GDM. Methods: A prospective cohort study was conducted to examine the effect of three exercise interventions - aerobic exercise (AE), resistance training (RT), and a combination of both (AE+RT) - on women with GDM. The primary outcomes measured were fasting blood glucose (FBG), 2-hour postprandial blood glucose (2h-PBG), and glycated hemoglobin A1c (HbA1c). The secondary outcomes included maternal pregnancy outcomes and neonatal birth outcomes. Results: A total of 184 participants were included in this study, with 145 completing all follow-up assessments. Time exhibit a statistically significant effect on FBG (p < 0.001), whereas the different intervention methods did not present a significant effect on FBG (p = 0.32). Furthermore, time exhibited a statistically significant effect on 2h-PBG (p < 0.001). Following the interventions, all exercise groups exhibited significantly lower 2h-PBG levels compared to the control group (all p values < 0.05). The three exercise interventions demonstrated significantly different effects on improving the maternal outcome of postpartum hemorrhage (p = 0.01). The combined AE+RT group exhibited the lowest volume of postpartum hemorrhage (254.09, standard deviation (SD) = 103.57). Regarding neonatal outcomes, the macrosomia outcome has statistically significant differences (p = 0.04), and other outcomes found no significant differences between the three exercise intervention groups and the control group (all p values ≥ 0.05). Conclusions: The combined AE+RT intervention demonstrated superior efficacy in reducing 2h-PBG, HbA1c levels, as well as postpartum bleeding, compared to the control group. Furthermore, a combination of AE+RT demonstrated greater efficacy in reducing 2h-PBG and HbA1c compared to single exercise groups. Therefore, combining AE+RT may be a more effective exercise regimen for managing of GDM in pregnant women. Clinical Trial Registration: The study has been registered on https://www.isrctn.com/ (registration number: ISRCTN40260907).